Environmental Impact Assessment av en musikfestival – Möjligheter och hinder - Arvidsson,Julia (2012)
The concept of sustainability for music festivals is increasingly important. Music festivals are associated with both environmental and social aspects through its impact on people attending the festival as well as its surroundings and nature. Until recently there has not been much guidance offered to help manage the environmental and social aspects of festivals. The guidance offered today has it’s focus solely on environmental aspects or fail to fully describe the aspects that arise from a music festival. This study aims to test the applicability of a Rapid Environmental Impact Assessment as a tool for describing and evaluating the social and environmental impact of music festivals. Based on a case study at the Reearth-festival in Koh Samui, Thailand, both the tool's applicability and the festival's impact was analyzed. The framework for the analysis was developed by Maria Osbeck, in collaboration with IUCN. The EIA was conducted in February this year at the festival at Koh Samui. Interviews with organizers, partners and vendors were made. A survey among the festival visitors was made. The Reearth-festival has a strong environmental profile and a willingness to spread an awareness of sustainable tourism and travel. It was found that the method was well applicable and that it covered most of the environmental aspects of the Reearth festival. The Environmental Impact Assessment covers both direct and indirect environmental aspects aswell as social aspects. One difficulty that emerged when using this method is that the large scope of the environmental and social aspects makes the end result a bit fragmented and therefore, difficult to analyze. Another difficulty was the lack of existing data, that regardless of method, complicates a fully credible analysis. It would be desirable to find a method that manages to cover both social and environmental issues fully, but which still allows for a holistic view of the festival. This to enable, to the greatest extent possible, to identify the environmental and social impacts and hence identify possibilities for improvements.